2014
DOI: 10.4049/jimmunol.1302913
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Catabolism Restricts IFN-γ–Expressing Neutrophils and Clostridium difficile Immunopathology

Abstract: The interplay between Clostridium difficile and the host's metabolome is believed to influence the severity of infection. However, the mechanism for this phenomenon remains unclear. In this study we model one of these metabolic pathways by focussing on tryptophan metabolism in the host. We found that inhibition of tryptophan catabolism in indoleamine 2,3-dioxygenase (IDO1) knockout mice led to increased mucosal destruction and cecal haemorrhage, increased production of IFNγ in response to C. difficile infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 40 publications
3
55
1
1
Order By: Relevance
“…For example, Romani et al [159] reported that impaired IDO1 activity in lung neutrophils is linked to the excessive immune response and ensuing chronic inflammation in a mouse model of CGD, whereas IDO1-expressing human eosinophils are capable of attenuating Th1 and supporting Th2 responses, although, in this study, the involvement of IDO1 was not directly investigated with an IDO1 inhibitor and/or L-Trp supplementation [50]. IDO1 expression, L-Trp depletion and production of Kyn have also been linked to increased neutrophil apoptosis [263], which may relate to reports of elevated neutrophil tissue infiltration and responses noted in Ido1 gene-silenced or -deficient mice subject to infection in vivo [263,264].…”
Section: Lymphocytesmentioning
confidence: 81%
See 2 more Smart Citations
“…For example, Romani et al [159] reported that impaired IDO1 activity in lung neutrophils is linked to the excessive immune response and ensuing chronic inflammation in a mouse model of CGD, whereas IDO1-expressing human eosinophils are capable of attenuating Th1 and supporting Th2 responses, although, in this study, the involvement of IDO1 was not directly investigated with an IDO1 inhibitor and/or L-Trp supplementation [50]. IDO1 expression, L-Trp depletion and production of Kyn have also been linked to increased neutrophil apoptosis [263], which may relate to reports of elevated neutrophil tissue infiltration and responses noted in Ido1 gene-silenced or -deficient mice subject to infection in vivo [263,264].…”
Section: Lymphocytesmentioning
confidence: 81%
“…Recent data indicate that C. difficile-infected IDO1 −/− mice show increased intestinal tissue destruction and haemorrhage that correlates with elevated numbers of IFNγ -expressing neutrophils, reduced C. difficile burden, but no change in effector or regulatory T-cells [263]. These data indicate that, rather than regulating T-cells and despite an increase in bacterial burden, IDO1 plays a protective role in moderating neutrophil tissue infiltration during C. difficile infection aimed at avoiding excessive inflammatory tissue damage and immunopathology that can be mediated by these innate immune cells.…”
Section: Micro-organism Induction Of Ido1 In Vivomentioning
confidence: 98%
See 1 more Smart Citation
“…Here, we demonstrate that in the regulation of innate cellular responses, PMN transepithelial migration is inhibited via the action of kynurenines, rather than by tryptophan limitation. Of note, one recent study showed diminished PMN recruitment to infected cecum in Ido1-deficient mice (43). In that paper, L-kynurenine was found to promote apoptosis of murine bone marrow-derived neutrophils, though only in tryptophan-deficient media.…”
Section: Discussionmentioning
confidence: 98%
“…Cecal cells were collected using a modified version of a previously published protocol 24 . IEL and lamina propria (LM) cells were analyzed by flow cytometry.…”
Section: Methodsmentioning
confidence: 99%